Deep phylogeographical structure and parallel host range evolution in the leaf beetle Agelasa nigriceps. Issue 2 (11th December 2013) - Kohyama, Tetsuo I.; Matsumoto, Kazuma; Katakura, Haruo
Abstract To understand the mechanisms behind the diversification of herbivorous insects through insect–plant interactions, it is important to know how the insects change their diet breadth in response to environmental changes. In this study, we investigated the phylogeographical pattern of the leaf beetle Agelasa nigriceps to infer the evolutionary history of its host range. While this beetle commonly uses Actinidia arguta (Actinidiaceae) as a host plant, it has been recorded recently on Pterostyrax hispidus (Styracaceae), which is now increasing in abundance at some localities in Japan due to the indirect effects of high population size of a mammalian herbivore. Considerable variation among populations in the ability of Ag. nigriceps to use P. hispidus suggests that P. hispidus is a newly acquired host plant for this beetle. Phylogenetic analyses using mitochondrial DNA sequences and amplified fragment length polymorphism (AFLP) revealed a high degree of phylogeographical structure in Ag. nigriceps throughout Japan, which is consistent with the hypothesis that several glacial refugia existed in the Japanese archipelago. In contrast, no genetic structure associated with the host plants was detected. Both the mitochondrial DNA and AFLP analyses showed that populations that can use P. hispidus are polyphyletic. These results and geographical variation in host use suggest that the host range expansion to a novel host, P. hispidus, is a very recent and possibly ongoing phenomenon and has occurred independently in several regions. Our study illustrates that the host range of herbivorous insects can evolve repeatedly in response to similar environmental changes.